Analysis and Speciation of Chromium in Environmental Matrices by Various Analytical Techniques - A Review - Rama Jyothi, N.; Mohammad Farook, N.A.; Cho, Migyung; Shim, Jaesool (Asian Journal of Chemistry, 2013)
Chromium is a very important metal due to its use in various industries, such as dye, pigments and stainless steel. Hexavalent chromium is a carcinogen. Its determination in various environmental segments is always a challenging issue for environmental researchers. In this concern first section of this review article gives a brief history of chromium, such as its oxidation states, production information, uses, biological importance, exposure pathways and regulatory concentration levels. The second section explains about the sources of chromium and the next section gives the details of health effects and toxicity caused due to the presence of chromium in various environmental segments. Finally, this paper discusses the determination of chromium in different biological and environmental samples by various analytical techniques, such as atomic absorption spectrometer, Spectrophotometer, Voltammeter, Inductively coupled plasma techniques (ICP-AES, OES), potentiometer, spectrofluorometer, HPLC/GC-MS and chemiluminescence reported by the researchers worldwide since 2006. All the data collected during the literature survey is tabulated, which gives important information about the analytical methods and techniques used for the chromium determination.